Ballast Water Treatment System Integration and Life Cycle Cost Analysis for Dry Bulk Carrier - Tokus, Mesut (CHAMBER MARINE ENGINEERS, 2019)
The ships use ballast water system in order to maintain their stability according to load conditions. Ballast water that is taken to ships' ballast tank contains various organism. These organisms may become invasive species when they have the chance to reproduce in the new ecosystem they are going to. These harmful organisms affect the ecology, economy and human health in regions where they go. For this reason, international organizations have been set standards and criteria related to ballast water management. IMO (International Maritime Organization) has D1 and D2 standarts related to ballas water trematment received in the International Convention for the Control and Management of Ship' Ballast Water and Sediments. According to the criteria taken by IMO, ballast water treatment systems have been examined under three main topics; mechanical, physical and chemical. Selection criteria have been established in agreement with the methods examined and ballast water treatment system has been selected for a sample dry cargo vessel with respect to these criteria. The integration of the selected UV + filtering system to the sample dry bulk carrier has been carried out. Besides, life cycle cost elements have been determined for the UV + filtering ballast water treatment system, cost structure has been formed and cost analysis has been carried out. The risks and uncertainties related with the life cycle costs of the product have been defined. The approximate cost of the system was found as (sic)400.000 and when cost breakdown was analyzed the biggest cost was found as the investment cost.
Keywords: Balast Water; Balast Water Treatment; UV + filtration; Life Cycle Cost Analysis; SHIP; Engineering; Transportation